Effect of Grain Size and Film Thickness on the Thermoelectric Properties of Flexible Sb2Te3 Thin Films - Pornsiri Wanarattikan; Piya Jitthammapirom; Rachsak Sakdanuphab; Aparporn Sakulkalavek (Advances in Materials Science and Engineering)
In this work, stoichiometric Sb2Te3 thin films with various thicknesses were deposited on a flexible substrate using RF magnetron sputtering. The grain size and thickness effects on the thermoelectric properties, such as the Seebeck coefficient (S), electrical conductivity (σ), power factor (PF), and thermal conductivity (k), were investigated. The results show that the grain size was directly related to film thickness. As the film thickness increased, the grain size also increased. The Seebeck coefficient and electrical conductivity corresponded to the grain size of the films. The mean free path of carriers increases as the grain size increases, resulting in a decrease in the Seebeck coefficient and increase in electrical conductivity. Electrical conductivity strongly affects the temperature dependence of PF which results in the highest value of 7.5 × 10−4 W/m·K2 at 250°C for film thickness thicker than 1 µm. In the thermal conductivity mechanism, film thickness affects the dominance of phonons or carriers. For film thicknesses less than 1 µm, the behaviour of the phonons is dominant, while both are dominant for film thicknesses greater than 1 µm. Control of the grain size and film thickness is thus critical for controlling the performance of Sb2Te3 thin films.